Electronic Criminal Record in Greece: Project Management Approach and Lessons Learned in Public Administration - Demetrios SARANTIS; Dimitris ASKOUNIS (Transylvanian Review of Administrative Sciences, 2009)
The implementation of eGovernment isa burgeoning phenomenon across the globe.However, a review of the IS literature reveals theinability of public administration organisationsto complete information technology projectssuccessfully. Unless governments learn tomanage the government transformation projects,these e-dreams will turn into global nightmares.The shortage of studies on eGovernmentimplementation presents a knowledge gap thatneeds to be plugged. This paper describes andanalyzes the computerisation of the existingpaper-based criminal record system in a publicorganisation in Greece. Our intent is to present anapplication of a goal driven project managementmethodology named eGTPM in order to use itas a methodological reference when navigatingin the open sea of information technologyproject implementations in the area of publicadministration. The successful implementation ofthe specific project indicates that the applicationof eGTPM approach could provide a solution toachieve government transformation objectivesmore effectively and efficiently.